2020
DOI: 10.1093/infdis/jiaa661
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Rates and Causes Among Persons With HIV in the United States and Canada, 2005–2015

Abstract: Background To assess the possible impact of antiretroviral therapy improvements, aging, and comorbidities, we examined trends in all-cause and cause-specific hospitalization rates among persons with HIV (PWH) from 2005 to 2015. Methods In six clinical cohorts, we followed PWH in care (≥1 outpatient CD4 count or HIV viral load [VL] every 12 months) and categorized ICD codes of primary discharge diagnoses using modified Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
10
2
Order By: Relevance
“…This may underestimate associations for factors likely to change over time such as HIV-related clinical factors, adverse lifestyle factors and mental health symptoms. The rate of hospitalisation of 5.8/100 person-years in our study population was lower than in some other recent studies in other high income settings [ 13 , [35] , [36] , [37] ]. Our study population had a high median CD4 count (621 cells/μl) and included a low proportion of individuals with recent diagnosis (3.6% of individuals were within their first year after diagnosis at baseline) for whom hospitalisation rates are particularly high [6] .…”
Section: Discussioncontrasting
confidence: 78%
“…This may underestimate associations for factors likely to change over time such as HIV-related clinical factors, adverse lifestyle factors and mental health symptoms. The rate of hospitalisation of 5.8/100 person-years in our study population was lower than in some other recent studies in other high income settings [ 13 , [35] , [36] , [37] ]. Our study population had a high median CD4 count (621 cells/μl) and included a low proportion of individuals with recent diagnosis (3.6% of individuals were within their first year after diagnosis at baseline) for whom hospitalisation rates are particularly high [6] .…”
Section: Discussioncontrasting
confidence: 78%
“…Recent studies in Illinois, North Carolina, and New York City also reported higher hospitalization rates for women compared with men and Black compared with White PWH [18][19][20]. A previous NA-ACCORD analysis found a small decrease in adjusted rates over time overall [27]. In this study, there was no change in adjusted rates stratified by race, ethnicity, and gender.…”
Section: Discussioncontrasting
confidence: 52%
“…This may underestimate associations for factors likely to change over time such as HIV-related clinical factors, adverse lifestyle factors and mental health symptoms. The rate of hospitalisation of 5.8/100 person-years in our study population was lower than in some other recent studies in other high income settings [13,[35][36][37]. Our study population had a high median CD4 count (621 cells/ml) and included a low proportion of individuals with recent diagnosis (3.6% of individuals were within their first year after diagnosis at baseline) for whom hospitalisation rates are particularly high [6].…”
Section: Discussionmentioning
confidence: 51%